2020
DOI: 10.1111/jocn.15583
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of wound care nurses’ practice in patients with pressure ulcers: An integrative review

Abstract: Background Wound care nurses are recognised as a key element for improving health outcomes. However, there is still fragmented knowledge of the outcomes associated with their practice in individuals with pressure ulcers. Aims and objectives To identify, summarise and map all available evidence related to the outcomes of wound care nurses’ practice in individuals with pressure ulcers. Design Integrative literature review. Review method To report the review, we followed the modified version of Cooper's five‐step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…13 As seen in the study by Monaco et al, 14 the presence of a wound care nurse may decrease PI incidence and treatment costs and improve healing. 14 The tracheostomy team leaders conducted a literature review and, with help from team members, explored best practices from other academic medical centers. They then assessed organizational policy to ensure that it reflected current evidence-based practice and evaluated existing and new products.…”
Section: Building the Teammentioning
confidence: 91%
See 1 more Smart Citation
“…13 As seen in the study by Monaco et al, 14 the presence of a wound care nurse may decrease PI incidence and treatment costs and improve healing. 14 The tracheostomy team leaders conducted a literature review and, with help from team members, explored best practices from other academic medical centers. They then assessed organizational policy to ensure that it reflected current evidence-based practice and evaluated existing and new products.…”
Section: Building the Teammentioning
confidence: 91%
“…Having certified wound nurses can be an important factor in achieving better outcomes in acute care settings 13 . As seen in the study by Monaco et al, 14 the presence of a wound care nurse may decrease PI incidence and treatment costs and improve healing 14 …”
Section: Methodsmentioning
confidence: 99%
“…An integrative literature review of 13 studies found that PI incidence, rate of healing, and time to heal were positively impacted by WOC nurse practice. 5 A retrospective analysis of NDNQI (National Database of Nursing Quality Indicators) data found that hospitals with WOC nurses had better HAPI rates and prevention strategies. 6 The occurrence of stages 3 and 4 PIs in organizations with WOC nurses was almost half that of organizations without At NewYork-Presbyterian Hospital, Mary Anne Gallagher, DNP, RN, Ped-BC, is Director of Nursing, Center for Professional Nursing Practice, and Natalia Chraplyvy, MBA, RN, is Process Improvement Lead, Financial Planning Department.…”
Section: Value Of Woc Nursesmentioning
confidence: 99%
“…Hiring a WOC nurse can bring financial, clinical, and reputational returns on investment. An integrative literature review of 13 studies found that PI incidence, rate of healing, and time to heal were positively impacted by WOC nurse practice 5 . A retrospective analysis of NDNQI (National Database of Nursing Quality Indicators) data found that hospitals with WOC nurses had better HAPI rates and prevention strategies 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Hiring a WOC nurse can bring financial, clinical, and reputational returns on investment. An integrative literature review of 13 studies found that PI incidence, rate of healing, and time to heal were positively impacted by WOC nurse practice 5. A retrospective analysis of National Database of Nursing Quality Indicators (NDNQI) data found that hospitals with WOC nurses had a lower HAPI rate and better prevention strategies 6.…”
Section: Value Of Woc Nursesmentioning
confidence: 99%